Systemic Inflammation Impairs Mood Function by Disrupting the Resting-State Functional Network in a Rat Animal Model Induced by Lipopolysaccharide Challenge - Xia Zhu; Mu-Huo Ji; Shu-Ming Li; Bin Li; Li Mei; Jian-Jun Yang (Hindawi Limited, 2019)
Background. Systemic inflammation impairs cognitive performance, yet the brain networks mediating this process remain to be elucidated. The purpose of the current study was to use resting-state functional magnetic resonance imaging (fMRI) to explore changes in the functional connectivity in a lipopolysaccharide- (LPS-) induced systemic inflammation animal model. Materials and Methods. We used the regional homogeneity (ReHo) method to examine abnormal brain regions between the control and LPS groups and then considered them as seeds of functional connectivity analysis. Results. Compared with the control group, our study showed that (1) LPS impaired mood function, as reflected by a depression-like behavior in the forced swim test; (2) LPS induced significantly increased ReHo values in the anterior cingulate cortex (ACC) and caudate putamen (CPu); (3) the ACC seed showed increased functional connectivity with the retrosplenial cortex, superior colliculus, and inferior colliculus; and (4) the right CPu seed showed increased functional connectivity with the left CPu. Linear regression analysis showed a LPS-induced depression-like behavior which was associated with increased ReHo values in the ACC and right CPu. Moreover, the LPS-induced depression-like behavior was related to increased functional connectivity between the right CPu and left CPu. Conclusion. This is the first study to show that systemic inflammation impairs mood function that is associated with an altered resting-state functional network based on ReHo analysis, providing evidence of the abnormal regional brain spontaneous activity which might be involved in inflammation-related neurobehavioral abnormalities.